Some cytological and physiochemical features relating to non-storability of pistachio (Pistacia vera L.) pollen. Issue 6 (2nd November 2018) - Zamani Bahramabadi, Elaheh; Jonoubi, Parissa; Rezanejad, Farkhondeh
Abstract: Pollen grains may become desiccated after independence from parent plants and remain viable in an inactive dry state during presentation and dispersal, until the conditions for rehydration and germination are prepared. But some pollen types do not tolerate the desiccation state and lose the germination power soon after release, and therefore, are difficult to store. In this study, moisture content, germinability, cytology and dehydrin and phenolics contents were surveyed in pistachio pollen at fresh and desiccated states. Mature pollen lost 54.1% of its initial moisture after 48 h desiccation along with severe decrease in germinability. Light microscopy results indicated that a low rate of pollen grains have vegetative cell rupture caused by desiccation, but a higher rate of grains were intact in appearance. Numerous amyloplasts persisted after desiccation as a sensitivity indicator. A 16 kDa dehydrin band was detected by western blot method with higher content in desiccated than fresh samples. High performance liquid chromatography (HPLC) analysis showed that the total content of phenolics increased slightly by desiccation. These results indicate the insufficiency of dehydrin and phenolics accumulation for achievement of desiccation tolerance. Furthermore, the severe loss of germinability in desiccated pistachio pollen may be the result of deficiency in some other protective mechanisms that need further investigations.